Persepsi Dosen dalam Pemilihan dan Pengembangan Bahan Ajar Drama - Dimas Anugrah Adiyadmo; Siti Gomo Attas; Ninuk Lustyantie (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study is to describe the lecturers' perceptions of the development of drama teaching materials. The data collection method uses a questionnaire and open interviews given to lecturers who are in charge of Drama courses. This study uses a quantitative approach. The qualitative data findings from the results of an open interview were analyzed by the steps of data reduction, data presentation, and data verification to obtain conclusions. The results showed lecturers perceiving that: (1) teaching materials available so far were still very limited, especially those relating to drama as a performance art, (2) presentation of existing teaching materials was still in the form of textbooks with an amount that was also still very lacking , (3) the description of the material in the teaching material is not yet equipped with audio-visual examples, detailed images, and steps in the practice of playing drama, especially about the elements that build the drama as a performance art, and (4) the material in the teaching material is there is not yet in line with the syllabus of drama courses. Conclusions, the need for further adaptation and development of teaching materials to bridge the gap in the needs of student drama learning with technological developments and the 4.0 revolution. Keywords: Perception, Lecturers, Development, Teaching Materials, Drama